Heart rate and energy system analysis: Study on men's doubles badminton - Arief, N. A.; Setijono, H.; Nurhasa (1st International Conference on Education Social Sciences and Humanities (ICESSHum 2019), 2019)
The more accurate athletes¡¦ physiological data, the easier it takes to maximize the performance. It is crucial to acknowledge the standard heart rate (HR) and energy system as the prerequisite of men's doubles badminton. This study aims to quantitatively analyze the standard HR during the game, while the anaerobic threshold was examined to determine the percentage of the energy system. Further, this study is descriptive research which utilized repeated measurement analysis using Polar Team to obtain data during the game in full competition system. In conclusion, the result indicates the average HR during the game is in a submaximal category and the extent of anaerobic energy system which determined from the anaerobic threshold that reached almost 50%.